2018
DOI: 10.15537/smj.2018.11.23303
|View full text |Cite
|
Sign up to set email alerts
|

Oncology nurses’ knowledge, practice, and confidence toward chemotherapy-induced peripheral neuropathy in Jordan

Abstract: Objectives:To assess the knowledge, practice, and confidence of oncology nurses toward chemotherapy-induced peripheral neuropathy (CIPN) among patients with cancer in Jordan.Methods:Descriptive, and cross sectional study was conducted on a convenience sample of 148 Jordanian registered oncology nurses recruited from a Specialized Oncology Center in Jordan. Data collection took place in June, 2015. As a data collection tool, the assessment of oncology nurses’ knowledge and practice-revised questionnaire was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
3
9
0
Order By: Relevance
“…Instead of working in silos, clinicians should consider a multi‐disciplinary approach and collaboration to develop a cohesive, proactive and individualised CIPN patient care plan. Consistent with earlier studies (Al‐Atiyyat & Banifawaz, 2018 ; Binner et al, 2011 ; Smith et al, 2014 ), clinicians reported limited knowledge and understanding about CIPN, especially among junior clinicians. This led to difficulties and challenges providing support and over reliance on oncologists for managing CIPN symptoms.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Instead of working in silos, clinicians should consider a multi‐disciplinary approach and collaboration to develop a cohesive, proactive and individualised CIPN patient care plan. Consistent with earlier studies (Al‐Atiyyat & Banifawaz, 2018 ; Binner et al, 2011 ; Smith et al, 2014 ), clinicians reported limited knowledge and understanding about CIPN, especially among junior clinicians. This led to difficulties and challenges providing support and over reliance on oncologists for managing CIPN symptoms.…”
Section: Discussionsupporting
confidence: 82%
“…The findings highlight the need for better connectedness of CIPN support and communication. Echoing findings from earlier studies (Al‐Atiyyat & Banifawaz, 2018 ; Binner et al, 2011 ; Smith et al, 2014 ; Taylor & Tanay, 2020 ), clinicians in our study emphasised the need for a clear treatment and action plan for CIPN. An organisational protocol for addressing issues was lacking.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Although, PHNs have crucial aspects to prevent foot ulcer. Another study also confirmed that lack of knowledge and skill among PHNs could impact on quality of health care services [13,14]. Some evidence DOI 10.18502/kls.v7i2.10287 also reported that sufficient knowledge on diabetes management was associated with perceived barriers in blood glucose monitoring [15], and medication adherence [16].…”
Section: Discussionmentioning
confidence: 73%